En nombre del pueblo. Destruyendo a Marbury v. Madison - Sanín Restrepo, Ricardo (2023)
This work is the first in a group of inquiries that looks to establish the importance of the last words in law. It pretends to respond the various versions of popular constitutionalism that tries to fix in the people and in their capability for self management the place of truth, without a complete depuration of the concept of people. This first step tackles approaches evolution of the confrontation between the “judicial revision” doing by the United States ́ Supreme Court and the popular constitutionalism, since the Larry Kramer’s text “The people themselves”.